Effects of annealing temperature on both radial supporting performance and axial flexibility of poly(L‐lactic acid) braided stents. Issue 22 (1st February 2021) - Tian, Yuan; Liu, Muqing; Liu, Wentao; Cheng, Jie; Wu, Gensheng; Han, Ting; Zhang, Yi; Zhao, Gutian; Ni, Zhonghua
Abstract: In this paper, the effects of annealing temperature on both radial supporting performance and axial flexibility of poly(L‐lactic acid) (PLLA) braided stents are studied. Stents are annealed at a series of temperatures ranging from 80 to 160°C for 1 h, then indicators of shaping effect, radial supporting performance, and axial flexibility are compared. Stents not annealed and annealed at 80°C cannot be completely shaped. In contrast, stents annealed at 100 to 160°C are well shaped showing radial shrinkage rate of 1.0 ± 0.2% and almost no axial elongation. The radial compressive force and axial force are gradually increased by 51.2% and 89.2%, respectively with the annealing temperature gradually increasing from 80 to 160°C, indicating that the radial supporting performance is improved but axial flexibility is weakened by a higher annealing temperature. Taken together, PLLA braided stents can be annealed at 100 to 120°C to obtain sufficient radial force and lower axial force simultaneously for clinical applications. Moreover, tensile test, X‐ray diffraction, and differential scanning calorimetry are performed for monofilaments annealed at different temperatures to further explore the effect mechanism of annealing temperature on the mechanical properties of stents. This study may provide helpful suggestions for the manufacture of biodegradable braided stents. Abstract : The mechanical properties of poly(L‐lactic acid) (PLLA) braided stents can be enhanced by optimizing the annealing temperature. A higher annealing temperature between the glass transition temperature and the melting temperature of PLLA improves the radial supporting performance of PLLA braided stents but weakens the axial flexibility. Taken together, PLLA braided stents can be annealed at 100 to 120℃ to obtain sufficient radial force and lower axial force simultaneously for clinical applications.